Formative assessment in the English as a foreign language classroom in secondary schools in Poland. Report on a mixed-method study - Baran-Łucarz, Małgorzata (Journal of Education Culture and Society, 2019)
Aim. The paper addresses the problem of formative assessment in the foreign language (FL) classroom. Its main objective is to present the outcomes of a study identifying tendencies related to the use of formative assessment during English lessons in Polish high schools, and students’ opinions on the frequency, type and effects of assessment they had been provided with during secondary school education. Methods. The data come from a retrospective study applying a mixed-method approach. They were gathered with a questionnaire based on a Likert scale, complemented with a few open-ended questions. The responses were provided by 106 students who graduated various high schools in the years 2014-2017 in 36 towns/cities located in different regions of Poland. The frequencies of using formative assessment in the case of all the FL skills and subskills are presented in comparison to summative assessment. The qualitative data were coded with an aim of finding some common trends. Results. The study showed that in the case of the participants of this research, formative assessment in secondary education at EFL classes was evidently neglected. Many students (approximately 25%) acknowledged to never having been provided with formative assessment with regards to pronunciation, receptive and productive skills. The open responses signal students’ awareness of the importance of feedback and of several negative effects resulting from the lack of its regular provision. Conclusions. The data gathered in the study seem to call for the need to raise the understanding of the role and the practical abilities to use formative assessment in the EFL classroom both at pre-service and in-service teacher training courses.